1990
DOI: 10.1111/j.1440-1827.1990.tb01607.x
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Carcinoid Tumor of the Lung, Associated with Giant‐cell Transformation in Bone Metastasis

Abstract: A case of neuroendocrine lung tumor located beneath the pleura in a 71 year old woman is reported. At autopsy, the tumor was found to have metastasized to the bones and liver without involving the hilar lymph nodes. Histological‐ly, the tumor cells at the primary site and in the liver metastasis exhibited a carcinoid‐like organoid structure, whereas pleomorphic giant cells were noted in the bone metastasis. The argyrophilic tumor cells were immuno‐reactive for neuron specific enolase, chromogranin A, serotonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Clinically, these tumors may be associated with carcinoid syndrome 31 and show a spectrum of cell differentiation that includes spindle cells and oncocytic and melanocytic features, among others. [32][33][34][35][36][37] However, other authors believe that the most accurate designation for these neoplasms is neuroendocrine carcinoma, which conveys the true nature of these tumors 22,38 and honors the previous classification of Gould et al, 19 in which atypical carcinoid is equivalent to well-differentiated neuroendocrine carcinoma. Important to mention about this designation of tumors is the lack of incorporation of the so-called tumorlet, which in reality may represent the true carcinoid (looks like carcinoma but is benign).…”
Section: Carcinoid and Atypical Carcinoidmentioning
confidence: 99%
“…Clinically, these tumors may be associated with carcinoid syndrome 31 and show a spectrum of cell differentiation that includes spindle cells and oncocytic and melanocytic features, among others. [32][33][34][35][36][37] However, other authors believe that the most accurate designation for these neoplasms is neuroendocrine carcinoma, which conveys the true nature of these tumors 22,38 and honors the previous classification of Gould et al, 19 in which atypical carcinoid is equivalent to well-differentiated neuroendocrine carcinoma. Important to mention about this designation of tumors is the lack of incorporation of the so-called tumorlet, which in reality may represent the true carcinoid (looks like carcinoma but is benign).…”
Section: Carcinoid and Atypical Carcinoidmentioning
confidence: 99%
“…CK, SYN, NSE and CGA are usually expressed in neoplastic cells of NE cell tumors (carcinoids) that develop in the nasal cavity, lung or gastrointestinal tract 13 , 16 , 17 . In addition, such neoplastic cells sometimes express serotonin, substance P, VIP, neuropeptide Y and protein gene product 9.5 18 , 19 . Therefore, the positive immunoreactivity for CK, SYN, VIP and CGA in the present case strongly suggested that the NE cell was the origin of this tumor.…”
Section: Introductionmentioning
confidence: 99%